Правова позиція: загальноправова характеристика - Лазарєв, В. В.; Lazariev, V. V.; Лазарєв Віктор Вікторович (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. - С. 20-31, 2023)
Статтю присвячено комплексному аналізу поняття «правова позиція». Виокремлено підходи дослідників до розуміння категорії «правова позиція». Наголошено на нерозривному зв’язку правової позиції з праворозумінням і правовою культурою. Наведено перелік найважливіших характеристик, притаманних правовим позиціям. Наголошено, що природу правових позицій утворює прагматика, ставлення людини до реальних речей. Зауважено, що категорію «правова позиція» слід розглядати ширше, ніж певні аргументи і переконання для прийняття рішення стосовно правозастосовної практики.

The research focuses on the fact that today the concept of “legal standpoint” is quite popular both in legal theory and practice, and is generally recognised in the national science, but there are different approaches to its understanding in the legal literature. An integrated analysis of the approaches to understanding the essence of this category has been conducted, and it has been established that modern scientific doctrine considers legal standpoint from different approaches: as part of legal culture and legal consciousness; as certain concepts, ideas; as part of an act or its conclusions. It has been noted that such approaches complicate the understanding of the very essence of a legal standpoint at the doctrinal level, and this may lead to contradictions in the implementation of legal provisions. That is why this term should be used in compliance with the rules of formal certainty. In order to clarify the legal nature of the term “legal standpoint”, it has been identified its main characteristics. It has been pointed out that the most important feature of a legal standpoint, its heart, is its main idea. An opinion that legal standpoint is a concept of the general theory of law has been supported. In this regard, the author provides an argument that legal standpoint is undoubtedly a product of mental activity, primarily of a professional. The concept is based on a principle, an idea, which is the basis for a proposal (version, hypothesis, recommendation, etc.) that provides a solution to any legal problem. It has been stated that the nature of legal standpoint is formed by pragmatism, a person's attitude to real things, which is noted by almost all researchers. When mastering a legal standpoint, certain philosophical approaches should be taken as a basis. In any case, it has been proposed to understand a legal standpoint as an assessment of factual reality and a system of arguments, conclusions and proposals for its legal regulation. This is a kind of logical and legal construction that expresses the attitude to law, legal regulation and its norms. Therefore, it has been established that a legal standpoint is a philosophical and legal category which includes a person’s mental activity, on the basis of which a certain proposal is built, which is used to ensure the resolution of any legal issue.

Статья посвящена комплексному анализу понятия «правовая позиция». Выделены подходы исследователей к пониманию категории «правовая позиция». Отмечена неразрывная связь правовой позиции с правопониманием и правовой культурой. Приведен список важнейших характеристик, характерных для правовых позиций. Отмечено, что природу правовых позиций образует прагматика, отношение человека к реальным вещам. Замечено, что категорию «правовая позиция» следует рассматривать более широко, чем определенные аргументы и убеждения для принятия решения по поводу правоприменительной практики.
Legal standpoint: general legal characteristics
Keywords: правова позиція; legal position; правовая позиция; праворозуміння; legal understanding; правопонимание; Конституційний Суд України; Constitutional Court of Ukraine; Конституционный Суд Украины; Верховний Суд; Supreme Court; Верховный Суд; правові ідеї; legal ideas; правовые идеи; філософські підходи; philosophical approaches; философские подходы